Analisis Pengembangan Objek Wisata Pemandian Manigom di Kabupaten Simalungun - Heru Frianto Simanjuntak; Siti Latifah; Muhdi Muhdi (Program studi Kehutanan USU, 2015)
Pemandian Manigom ecotourism is a target destination in Simalungun. Management of Pemandian Manigom ecotourism not optimal so that this attraction is rarely visited by tourists. This study aimed to analyze potency of the development, problems and the development srategy of Pemandian Manigom ecotourism. The potential object of Pemandian Manigom region are flora and fauna, very beautiful natural scenery, path tracking, and camping ground area. This ecotourism has appeal, accessibility, accommodation, facilities, and infrastructure with percentage of the egibility rate was 93,92%. In the SWOT analysis, Pemandian Manigom ecotourism are a very favorable situation which quadrant I that it has the power and more opportunities and can cover the weaknesses and threats in the development of attraction it.Keyword: Ecotourism, Pemandian Manigom, evaluation, SWOT analysis